Association between the number of teeth and frailty among Chinese older adults: a nationwide cross-sectional study. Issue 10 (22nd October 2019) - Gu, Yaohua; Wu, Wenwen; Bai, Jinbing; Chen, Xuyu; Chen, Xiaoli; Yu, Liping; Zhang, Qing; Zou, Zhijie; Luo, Xianwu; Pei, Xianbo; Liu, Xin; Tan, Xiaodong
Abstract : Objectives: To explore the association between the number of teeth and frailty among older Chinese adults using a nationally representative sample. Design: Cross-sectional analysis was carried out using the 2014 wave data from the Chinese Longitudinal Healthy Longevity Survey, which used a targeted random-sampling design. Setting: This research was conducted in communities from nearly half of the counties and cities in 22 out of 31 provinces throughout China. Participants: Of the 6934 interviewees aged ≥65 years, the final analysis included 3635 older adults who had completed the 2014 wave survey on the variables included in the study. Primary and secondary outcome measures: Outcome variables included frailty, measured by the Frailty Index, and number of teeth. Covariates included demographic characteristics (ie, age, sex, co-residence, marital status, years of education and financial support), body mass index (BMI) and health behaviours (ie, smoking, drinking and exercise). A univariate logistic regression was used to test the factors associated with frailty. A multiple logistic regression model was used, using the frailty score as the dependent variable and the number of teeth together with significant covariates as the independent variables. Results: The prevalence of frailty was 27.68%. The mean number of teeth present was 9.23 (SD=10.03). The multiple logistic regression showed that older adults' demographic variables, health behaviours, BMI, tooth number and chewing pain were significantly associated with frailty. After adjusting for the covariates, older adults with fewer teeth had significantly higher odds of frailty than those with 20 or more teeth (no teeth: OR=2.07, 95% CI 1.53 to 2.80; 1 to 10 teeth: OR=1.77, 95% CI 1.31 to 2.38), except for older adults with 11 to 20 teeth (OR=1.30, 95% CI 0.93 to 1.82). Conclusions: The presence of fewer teeth is significantly associated with frailty status among older Chinese adults. Future studies are needed to explain the specific mechanisms underlying how oral health status is associated with frailty.